Black feminist voices in politics - Simien, Evelyn M., 1974- (State University of New York Press, 2006)
"In Black Feminist Voices in Politics, Evelyn M. Simien charts a course for black women's studies in political science. Examining the simultaneous effects of race and gender on political behavior, Simien uses a national telephone survey sample of the adult African American population to discover the extent to which black women and men support black feminist tenets. At the heart of this book are answers to such questions as: How does the absence of black feminist voices impair our understanding of group consciousness? What factors make individuals more of less likely to adopt black feminist views? Are men just as likely as women to support black feminist tenets? Simien analyzes the survey data, responds to limitations of existing research, and addresses critical questions that many black academics, intellectuals, and activists have devoted significant energy to debating without much empirical evidence."--Jacket.